55.0k views
4 votes
Consider how the methods of undetermined coefficients and variation of parameters can be combined to solve the given differential equation. Carry out your ideas to solve the differential equation. y'' − 2y' + y = 4x2 − 6 + x−1ex

2 Answers

5 votes

Answer:

Combining the method of undetermined coefficients with the method of variation of parameters, the solution to the differential equation

y'' - 2y' + y = 4x² - 6 + x^(-1)e^x

is

y = (C1 + C2x)e^x + 4x² + 16x + 18 -xe^x + xe^x lnx

Explanation:

Given the differential equation:

y'' - 2y' + y = 4x² - 6 + x^(-1)e^x........(1)

Firstly, we solve the homogeneous part of (1)

y'' - 2y' + y = 0

Let the characteristic equation be

m² - 2m + 1 = 0

(m - 1)(m - 1) = 0

m = 1 twice.

The complementary function

y_c = (C1 + C2x)e^x...........................(2)

Now, consider the differential equation:

y'' - 2y' + y = 4x² - 6 ..........................(3)

Solve (3) using the method of UNDETERMINED COEFFICIENTS.

The nonhomogeneous part is 4x² - 6, so we assume a particular solution of the form

y_p = Ax² + Bx + C

y'_p = 2Ax + B

y''_p = 2A

Using these in (3), we have

y''_p - 2y'_p + y_p

= 2A - 2(2Ax + B) + Ax² + Bx + C = 4x² - 6

Ax² + Bx - 4Ax - 2B + 2A + C = 4x² - 6

Comparing the coefficients of various powers of x, we have that

A = 4

B - 4A = 0 => B = 16

2A - 2B + C = -6

=> C = -6 - 8 + 32 = 18

Therefore,

y_p = 4x² + 16x + 18 .....................(4)

Next, consider the differential equation:

y'' - 2y' + y = x^(-1)e^x ....................(3)

We solve using the method of VARIATION OF PARAMETERS.

With g(x) = x^(-1)e^x

Using the complementary solution, we have

y1 = e^x, and y2 = xe^x

Find the Wronskian of y1 and y2.

Let their Wronskian be W, then

W = |y1............y2|

........|y1'...........y2'|

= |e^x.....................xe^x|

...|e^x...........xe^x + e^x|

= xe^(2x) + e^(2x) - xe^(2x)

W = e^(2x)

y_q = Py1 + Qy2

Where P = integral of y2g(t)/W dx

= integral of xe^x.x^(-1)e^x/e^(2x) dx

= -x

Where Q = integral if y1g(t)/W dx

= integral of e^x.x^(-1)e^x/e^(2x) dx

= lnx

y_q = -xe^x + xe^x lnx

Finally, the general solution is

y = y_c + y_p + y_q

= (C1 + C2x)e^x + 4x² + 16x + 18 -xe^x + xe^x lnx

User DhaRmvEEr SiNgh
by
6.3k points
6 votes

Answer:

y = -xe^x + xe^x ln(x) +C

See attachment for step by step guide please

Consider how the methods of undetermined coefficients and variation of parameters-example-1
Consider how the methods of undetermined coefficients and variation of parameters-example-2
User Macro
by
5.7k points